Evaluation of BEBIG HDR 60Co system for non-invasive image-guided breast brachytherapy - Zehtabian, Mehdi; Sina, Sedigheh; Rivard, Mark J.; Meigooni, Ali S. (Journal of Contemporary Brachytherapy, 2015)
Purpose : HDR 60 Co system has recently been developed and utilized for brachytherapy in many countries outside of the U.S. as an alternative to 192 Ir. In addition, the AccuBoost® technique has been demonstrated to be a successful non-invasive image-guided breast brachytherapy treatment option. The goal of this project is to evaluate the possibility of utilizing the BEBIG HDR 60 Co system for AccuBoost treatment. These evaluations are performed with Monte Carlo (MC) simulation technique. Material and methods : In this project, the MC calculated dose distributions from HDR 60 Co for various breast sizes have been compared with the simulated data using an HDR 192 Ir source. These calculations were performed using the MCNP5 code. The initial calculations were made with the same applicator dimensions as the ones used with the HDR 192 Ir system (referred here after as standard applicator). The activity of the 60 Co source was selected such that the dose at the center of the breast would be the same as the values from the 192 Ir source. Then, the applicator wall-thickness for the HDR 60 Co system was increased to diminish skin dose to levels received when using the HDR 192 Ir system. With this geometry, dose values to the chest wall and the skin were evaluated. Finally, the impact of a conical attenuator with the modified applicator for the HDR 60 Co system was analyzed. Results: These investigations demonstrated that loading the 60 Co sources inside the thick-walled applicators created similar dose distributions to those of the 192 Ir source in the standard applicators. However, dose to the chest wall and breast skin with 60 Co source was reduced using the thick-walled applicators relative to the standard applicators. The applicators with conical attenuator reduced the skin dose for both source types. Conclusions : The AccuBoost treatment can be performed with the 60 Co source and thick-wall applicators instead of 192 Ir with standard applicators.